PENERAPAN PROSEDUR AUDIT TERHADAP ASET TETAP PADA PT SEN OLEH KAP TERAMIHARDJA, PRADHONO, DAN CHANDRA - Basuki Hidayat (2022)
Audit procedures are activities of testing account balances in financial statements that are used in forming an opinion or assessing whether the financial statements are presented fairly. Fixed assets are tangible objects owned by the company and used to support the company's operational activities. Fixed assets for companies are very important in producing goods or services, and the recording of additions and subtractions of fixed assets must be per applicable standards. Audit procedures for fixed asset accounts at PT SEN were conducted by KAP Teramihardja, Pradhono, and Chandra. This report aims to find out the audit procedures for fixed assets. Audit procedures are carried out systematically by planning audits, determining materiality, and conducting audits under the audit program. In the audit program, there are procedures for carrying out activities, such as analytical additions and deductions for fixed assets, physical inspections of fixed assets, and checking the calculation of depreciation of fixed assets. So it can be concluded that fixed assets in 2021 are presented and disclosed fairly by the audit assertions and there are no misstatements.